Diversity of coelomocytes in the class Echinoidea (Echinodermata): A comparative study based on morphological evidence - Vinicius Queiroz; Márcio R. Custódio (Comparative Immunology Reports)
Echinoidea is, by far, the most known echinoderm class regarding the coelomocytes and their physiological functions. However, a careful examination shows that most data deal with regular echinoids (sea urchins), leaving a gap regarding the irregular species (sand dollars and heart urchins). Most studies about irregular echinoids are purely descriptives, and the number of cell types is poorly known. Thus, the present study aims to investigate the diversity of cell types in Echinoidea and how they are distributed in the different internal taxa. Based on direct observations and a literature survey, we found 15 cell types in the class Echinoidea, which included phagocytes (three subpopulations), fusiform cells, progenitor cells, vibratile cells, and spherulocytes (eight subpopulations). Sea urchins showed a lower coelomocyte diversity compared to irregular echinoids. Considering only the irregular species, we found that sand dollars (Neognathostomata) presented a higher cell diversity than heart urchins (Atelostomata). Thus, our work shows that the diversity of coelomocytes in Echinoidea is still underestimated, and the generalizations should be avoided. Still, the lack of data on irregular echinoids impairs understanding their coelomocyte physiology.